Nachhaltigkeit von Infrastrukturbauwerken - Ganzheitliche Bewertung von Autobahnbrücken unter besonderer Berücksichtigung externer Effekte - Zinke, Tim (Berichte zum Stahl- und Leichtbau / Karlsruher Institut für Technologie, Versuchsanstalt für Stahl, Holz und Steine, Stahl- und Leichtbau, 2016)
Bridges are an important part of our traffic infrastructure and their functional capability is a basic requirement for mobility and transport. Holistic analyses have to incorporate aspects like the economic and ecologic performance within the complete life-cycle as well as interdependencies between the structure and traffic by calculating site-induced external effect as basis for a decision making process. These calculation and integration methods for bridges are provided by this thesis.